Economic Development of the Arab Countries : Selected Issues. (International Monetary Fund, 1993)
IMF economists work closely with member countries on a variety of issues. Their unique perspective on country experiences and best practices on global macroeconomic issues are often shared in the form of books on diverse topics such as cross-country comparisons, capacity building, macroeconomic policy, financial integration, and globalization.